Sociodemographic and Obstetric Characteristics of Anaemic Pregnant Women Attending Antenatal Clinic in Bolgatanga Regional Hospital. (3rd May 2016) - Ahenkorah, Benjamin; Nsiah, Kwabena; Baffoe, Peter
Abstract : The study determined the sociodemographic and obstetric characteristics of pregnant women which contribute to the risk of developing anaemia. A cross-sectional study was conducted among 400 pregnant women attending their first antenatal visit at the Bolgatanga Regional Hospital Antenatal Clinic. Anaemia was significantly associated (p < 0.05 ) with younger maternal age, parity, gravidity, trimester of pregnancy, and source of drinking water. Multivariate logistic regression identified the following factors with adjusted odds ratios (aOR) and 95% confidence intervals (CI): unemployment (aOR = 4.76 (CI: 2.26–11.33);p < 0.0001 ), rural dwelling (aOR = 3.10 (CI: 2.16–4.91);p = 0.0071 ), primigravida (aOR = 2.13 (CI: 1.34–3.18);p = 0.0201 ), nulliparity (aOR = 1.92 (CI: 1.23–2.86);p = 0.0231 ), first antenatal visit at second trimester (aOR = 1.71 (CI: 1.33–3.12);p = 0.0149 ) and first antenatal visit at third trimester (aOR = 2.73 (CI: 1.24–4.35);p = 0.0017 ), drinking from well and boreholes (aOR = 2.78 (CI: 2.27–5.21);p < 0.0001 ), and the presence of domestic livestock (aOR = 2.15 (CI: 1.33–3.68);p = 0.0019 ). This study has shown the various sociodemographic and obstetric factors which significantly contribute to anaemia in pregnancy.